PERANAN HASIL HUTAN BUKAN KAYU TERHADAP PENDAPATAN MASYARAKAT DI DESA CINTARAKYAT KECAMATAN SIBOLANGIT KABUPATEN DELI SERDANG - Bifrenta Ginting; Rudianda Sulaeman; Evi Sribudiani (Fakultas Pertanian, Universitas Riau, 2018)
Non-Timber forest products are both bio-vegetable and animal biodiversity products and their derivative and cultivation products except for timber. The role of non-timber forest product in the village of people’s love affects three aspects: it plays a role in helping the economy, labor and education. The types of non timber forest products utilized by the people of Cintarakyat village are palm sugar, gelugur acid, rubber, cinnamon, arecanut and candlenut. The average income earned by the villagers Cintarakyat from the use of non-timber forest products is Rp. 19.796.100,-/head of household per year and the average income beyond the utilization of non-timber forest products is Rp. 8.634.100,-/head of household per year.